On the lower bound of the Gauss curvature of a strictly convex closed surface - Babenko, V. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
The lower bound for the Gauss curvature on a strictly convex closed surface by its two integral parameters (width and radius of the circumscribed ball) are obtained.